Emotional Induction Through Music: Measuring Cardiac and Electrodermal Responses of Emotional States and Their Persistence - Ribeiro, Fabiana Silva; Santos, Flávia Heloísa; Albuquerque, Pedro Barbas; Oliveira-Silva, Patrícia (Frontiers in Psychology, 2019)
Emotional inductions through music (EIM) procedures have proved to evoke genuine emotions according to neuroimaging studies. However, the persistence of the emotional states after being exposed to musical excerpts remains mostly unexplored. This study aimed to investigate the curve of emotional state generated by an EIM paradigm over a 6-min recovery phase, monitored with valence and arousal self-report measures, and physiological parameters. Stimuli consisted of a neutral and two valenced musical excerpts previously reported to generate such states. The neutral excerpt was composed in a minimalist form characterized by simple sonorities, rhythms, and patterns; the positive excerpt had fast tempo and major tones, and the negative one was slower in tempo and had minor tone. Results of 24 participants revealed that positive and negative EIM effectively induced self-reported happy and sad emotions and elicited higher skin conductance levels (SCL). Although self-reported adjectives describing evoked-emotions states changed to neutral after two minutes in the recovery phase, the SCL data suggests longer lasting arousal for both positive and negative emotional states. The implications of these outcomes for musical research are discussed.